Effects of adhesive systems at different temperatures on the shear bond strength of orthodontic brackets - Serdar Akarsu; Suleyman Kutalmış Buyuk; Ahmet Serkan Kucukekenci (Tabriz University of Medical Sciences, 2019)
Background. The temperature might affect the physical and mechanical properties of adhesive materials by reducing the polymerization rate. The present study aimed to evaluate the effect of temperature on the shear bond strength of metallic orthodontic brackets using various adhesive resin systems. Methods. Extracted human premolar teeth were randomly assigned to 8 groups (n=10) for bonding with the two available orthodontics adhesive systems (Transbond XT and NeoBond) at different temperatures: refrigeration temperature (4°C), room temperature (20°C), human body temperature (36°C) and high temperature (55°C). The shear bond strength (SBS) test was performed using a universal testing machine at a crosshead speed of 0.5 mm/min. The adhesive remnant index (ARI) was assigned to the fractured orthodontic brackets. Data were analyzed with one-way ANOVA, post hoc Tukey tests and independent t-test. Results. Transbond XT exhibited higher SBS values compared to Neobond at all the tested temperatures; however, a statistically significant difference was not observed (P>0.05). The SBS results were minimum at 4°C and maximum at 36°C in both the adhesive groups (P<0.05). Conclusion. Pre-heating orthodontic adhesives up to the body temperature prior to bonding the brackets in orthodontic treatment increased the bond strength of orthodontic brackets.